Long noncoding RNA AOC4P regulates tumor cell proliferation and invasion by epithelial–mesenchymal transition in gastric cancer. (February 2019) - Zhang, Kecheng; Lu, Canrong; Huang, Xiaohui; Cui, Jianxin; Li, Jiyang; Gao, Yunhe; Liang, Wenquan; Liu, Yi; Sun, Yang; Liu, Hanxuan; Wei, Bo; Chen, Lin
Background: The clinical relevance and biological role of tissular AOC4P in gastric cancer (GC) remains to be clarified. Methods: The association between AOC4P expression and clinicopathological characteristics was investigated. In vitro, 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT), colony formation, wound healing and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assays were performed to explore the biological effects of AOC4P on GC cell proliferation, migration, invasion, and apoptosis in MGC-803 and BGC-823 cell lines. In vivo, animal experiments were conducted to confirm the in vitro findings. Quantitative real-time polymerase chain reaction, western blotting, and immunofluorescence were used to investigate the potential mechanisms. Results: Expression levels of AOC4P were significantly higher in tumor tissues than in noncancerous tissues, and patients with high levels of AOC4P had poor overall and disease-free survival. AOC4P expression was correlated with lymphovascular invasion. In vitro, knockdown of AOC4P inhibited tumor cell proliferation, migration, and invasion, and promoted apoptosis of MGC-803 and BGC-823 cells. In vivo, BGC-823 cells transfected with AOC4P siRNA formed smaller and lighter tumors than BGC-823 cells transfected with negative control siRNA in severe combined immunodeficiency mice. Additionally, the si- AOC4P group had less proliferating cells and more apoptotic cells in tumor xenografts compared with the negative control. Mechanistically, knockdown of AOC4P decreased the expression of vimentin and MMP9, while increasing the expression of E-cadherin. Immunofluorescence confirmed the relationship between AOC4P expression and E-cadherin, vimentin, and MMP9 levels in clinical GC specimens. Conclusions: AOC4P promotes tumorigenesis and progression partly through epithelial–mesenchymal transition in GC. Additionally, AOC4P may serve as a prognostic biomarker for clinical decision making.